KAJIAN LOYALITAS MAHASISWA (studi pada FE Universitas Negeri Manado) - Rondonuwu, Donald Bismarck (Jurnal Equilibrium, 2020)
To be able to win the competition, an institution must be able to provide more "value" to its customers compared to its competitors. In this context, the main customers of a university are students as users of education services and the world of work. This research shows that the cognitive commitment construct that has the most impact on student loyalty construct is the cognitive commitment to the institution. Then together with the cognitive commitment to the institution, both perceived quality of teaching services, trust in the institution's personnel, and emotional commitment to the institution have a strong and significant positive impact on student loyalty. Emotional commitment in this study was not influenced strongly and significantly by the integration of students towards their environment (academic integration and social integration) or their external commitments (job commitment, family commitment and non-university commitment). However, emotional commitment is still strongly and significantly influenced by trust in the institution's personnel and perceived quality of teaching services. In addition, trust in the institution's personnel is strongly and significantly influenced by perceived quality of teaching services.